Family partnering in practice: The role of caregivers’ epistemological theories in their interaction with families - Saglietti, Marzia; Zucchermaglio, Cristina (Adoption & fostering, 2025)
Research on alternative care – combined with evidence from family therapy and perspectives from children’s rights debates – robustly demonstrates that a crucial factor influencing the success of alternative care projects is family partnering, that is, maintaining relational continuity with birth families and participating with them, whenever it is judicially approved. However, there is a limited understanding of how this unfolds in practice. To address this gap, this article presents an in-depth ethnographic and conversation analytic study conducted in three group homes in Rome, Italy, aiming to thoroughly analyse interactions with families in light of family partnering. Drawing on ethnographic field notes, environmental documentation and video-recorded dinnertime interactions, in this study we build on Fruggeri’s work (1997, 2005) on the epistemological models of family interaction. Through this analysis, we contribute to the understanding of family partnering by illustrating caregivers’ pivotal role in either promoting or undermining family relational continuity and preventing or increasing children’s alienation. In conclusion, we suggest practical implications for alternative care and propose future avenues for exploring interactions with birth families in greater detail. Plain language summary Research shows that keeping children in contact with their birth families is a key factor in the success of alternative care placements. Where possible, families should stay involved in a child’s life, but there is little understanding of how this actually happens in practice in everyday life. This study looks at real-life interactions between caregivers and families in three group homes in Rome, Italy. By analysing field notes, observations, documents and recorded mealtime conversations, the research explores how caregivers can either help maintain family connections or unintentionally push children further away from their families. The findings highlight the important role of caregivers and suggest ways to improve family involvement in alternative care settings. The study also points out future directions for research on family relationships in these environments.